Quality of weight loss advice on Internet forums - Hwang, Kevin O. (2007)
BACKGROUND: Adults use the Internet for weight loss information, sometimes by participating in discussion forums. Our purpose was to analyze the quality of advice exchanged on these forums. METHODS: This was a retrospective analysis of messages posted to 18 Internet weight loss forums during one month in 2006. Advice was evaluated for congruence with clinical guidelines; potential for causing harm; and subsequent correction when it was contradictory to guidelines (erroneous) or potentially harmful. Message- and forum-specific characteristics were evaluated as predictors of advice quality and self-correction. RESULTS: Of 3368 initial messages, 266 (7.9%) were requests for advice. Of 654 provisions of advice, 56 (8.6%) were erroneous and 19 of these 56 (34%) were subsequently corrected. Forty-three (6.6%) provisions of advice were harmful and 12 of these 43 (28%) were subsequently corrected. Messages from low-activity forums (fewer messages) were more likely than those from high-activity forums to be erroneous (10.6% vs. 2.4%, p<0.001) or harmful (8.4% vs. 1.2%, p<0.001). In high-activity forums, 2 of 4 (50%) erroneous provisions of advice and 2 of 2 (100%) potentially harmful provisions of advice were corrected by subsequent postings. Compared to general weight loss advice, medication-related advice was more likely to be erroneous (p=0.02) or harmful (p=0.01). CONCLUSIONS: Most advice posted on highly-active Internet weight loss forums is not erroneous or harmful. However, clinical and research strategies are needed to address the quality of medication-related advice.